2005
DOI: 10.1099/mic.0.28193-0
|View full text |Cite
|
Sign up to set email alerts
|

Intragenomic recombination in the highly leukotoxic JP2 clone of Actinobacillus actinomycetemcomitans

Abstract: The highly leukotoxic JP2 clone of Actinobacillus actinomycetemcomitans is strongly associated with aggressive periodontitis in adolescents of African descent. DNA fingerprinting using the frequently cutting restriction enzyme MspI and multilocus sequence typing (MLST) showed that five strains of this clone were genetically virtually identical, although ribotyping of the six rrn genes and EcoRI RFLP analysis of the seven IS150-like elements revealed differences. PCR analyses demonstrated that these multi-cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…We have previously shown that PFGE using the rare cutting restriction enzyme XhoI can reveal genomic rearrangements in strains belonging to the JP2 clone (15). By using this method 34 different XhoI DNA fingerprints were obtained for the 82 A. actinomycetemcomitans strains studied.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that PFGE using the rare cutting restriction enzyme XhoI can reveal genomic rearrangements in strains belonging to the JP2 clone (15). By using this method 34 different XhoI DNA fingerprints were obtained for the 82 A. actinomycetemcomitans strains studied.…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that this technique reveals considerable polymorphism, even among members of the JP2 clone, due to intragenomic inversions resulting from homologous recombination between multicopy sequences in the genome (15). We therefore tested the applicability of this technique for studies of the local epidemiology of the JP2 clone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations